Islamic Perspective On Elective Abortion Of Zika Virus Infected Pregnant Women - Syazwani Hamdan; Mohammad Naqib Hamdan; Ummu Aiman Faisal; Mohd Rahman Omar (Faculty of Medicine and Health Sciences, University Putra Malaysia, 2024)
1ST INTERNATIONAL BORNEO HEALTHCARE AND PUBLIC HEALTH CONFERENCE AND 4TH BORNEO TROPICAL MEDICINE AND INFECTIOUS DISEASE CONGRESS Held at the Faculty of Medicine and Health Sciences, Universiti Malaysia Sabah, Kota Kinabalu, Sabah, Malaysia On 3rd-5th September 2019 Malaysian Journal of Medicine and Health Sciences (Volume :15 Supp 6)